ERGO-DESIGN AND CONTENT DEVELOPMENT CONSIDERATIONS FOR AN INTERACTIVE MULTIMEDIA KIOSK - Windharto, Agus; Prabowo, S. Heru (Institute of Research and Community Outreach - Petra Christian University, 2006)
Basic aspects of user interface design related to human cognitive system have been considered into most computer software applications recently especially those applications using the standard of Graphical User Interface (GUI). But different from the most software applications designed intentionally for user that assumed had been familiar to any computer application before, The User Interface for Public Kiosk System should be designed for users those could be possibly anyone totally unfamiliar with any computer interface system. Computer Illiterate User should be taken into interface design consideration, hence the basic aspects of human cognitive system should be considered as one of the most important factor in designing more intuitive and user friendly interface system model.This paper is a part of our research in the National Research Competition: Riset Andalan Perguruan Tinggi dan Industri (RAPID) programme 2004-2006 Sponsored by Ditjen DIKTI (General Directorate of Higher Education). The title of the research is :